PROSES MANUSIA DIHADIRKAN DAN AKHIRNYA LENYAP DALAM KETERBATASAN BAHASA - Ulfa, Ruzqiyah (Universitas Merdeka Malang, 2017)
Foucault opens this book with a direct introduction to the concept of heterotopia. The term heterotopia is a neologism that Foucault deemed so frightening, for he